Traditional Goddess worship culture of Tamil society and its impact on cinematic screen portray of this generation - P, Panbu Selvan; V, Ilamparithi (International Research Journal of Tamil, 2022)
The life of Ancient Tamil people was beautiful and full of emotions. They were the ones who gained great knowledge and experience from every phase of their lives. The knowledge and experience conserved, concocted and passed on in fragments by older generations. The people had begun to transform their love into worship and celebration. They preserved it in various art forms such as rhetoric, storytelling, painting, sculpture, street play, drama and literature for the future generations to know and cherish it. Different forms of media play a special role in transferring the same to people. Among these, cinema holds a pivotal space. The film captures the social structure born out of the aforementioned people's faith and conveys it through its story, shedding its light in the minds of the people. It is natural for people’s overwhelming beliefs to be reflected as stories of God and Goddesses. This article describes the worship of goddesses in literature and its relation to celebrating female actors on-screen in and by a Tamil society.